Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1063/1.2967192
|View full text |Cite
|
Sign up to set email alerts
|

Tunable split-ring resonator for metamaterials using photocapacitance of semi-insulating GaAs

Abstract: We report a method for tuning a split-ring resonator (SRR) using infrared light. The SRR unit cells are commonly used in arrays to form a metamaterial that exhibits an effective negative permeability and are often used in negative-refractive-index materials. The region of negative permeability is generally limited to a narrow bandwidth at a fixed frequency. In this work, we use photocapacitance as observed in undoped semi-insulating GaAs to modify the gap capacitance of a SRR. We demonstrate a continuously tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…This includes modification of the substrate parameters (e.g. permittivity) [4,5], the use of liquid crystals [6][7], lumped capacitors or varactors [8][9][10][11][12], ferromagnetic [13,14] and ferroelectric [15,16] techniques, semiconductors [17][18][19], microelectromechanical (MEMS) switches [20][21][22], and tuning based on near-field interactions between adjacent SRRs [23][24][25][26][27]. This last approach is the topic of the present study.…”
mentioning
confidence: 99%
“…This includes modification of the substrate parameters (e.g. permittivity) [4,5], the use of liquid crystals [6][7], lumped capacitors or varactors [8][9][10][11][12], ferromagnetic [13,14] and ferroelectric [15,16] techniques, semiconductors [17][18][19], microelectromechanical (MEMS) switches [20][21][22], and tuning based on near-field interactions between adjacent SRRs [23][24][25][26][27]. This last approach is the topic of the present study.…”
mentioning
confidence: 99%
“…Ring resonators have been extensively studied and shown to possess distinct functionalities in integrated optics on a variety of platforms, such as semiconductors [5], high index contrast dielectric waveguide [6] and metal-insulator-metal (MIM) waveguides [7]. Recently, various tunable resonators have been proposed and demonstrated to achieve tunable resonances using nematic liquid crystals [8], the photocapacitance of semi-insulating GaAs [9] or the thermo-optical effect [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is possible to achieve the manipulation over the structure via altering the resonance conditions. For example, simulations and experiments performed at microwave frequencies have shown that metamaterials can be controlled by mounting varactors or photocapacitances to their inner structures [12][13][14][15]. In [3], the authors proposed a tunable LHM based on the broadside-coupled SRR (BC-SRR).…”
Section: Introductionmentioning
confidence: 99%